1986
DOI: 10.1093/oxfordjournals.aje.a114231
|View full text |Cite
|
Sign up to set email alerts
|

Existence of Consistent Hypo- And Hyperresponders to Dietary Cholesterol in Man1

Abstract: Hyper- and hyporesponsiveness of serum cholesterol to dietary cholesterol is an established concept in animals but not in man. The authors studied the stability of the individual response of serum cholesterol to dietary cholesterol in three controlled experiments in 1982. The subjects were volunteers from the general population living in or near Wageningen, the Netherlands. Each experiment had a low-cholesterol baseline period (121, 106, and 129 mg/day in experiments 1, 2, and 3, respectively) and a high-chole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
1
2

Year Published

1992
1992
2012
2012

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 242 publications
(101 citation statements)
references
References 0 publications
4
92
1
2
Order By: Relevance
“…[23][24][25] The range of the response to changes in the amount or type of dietary fat and cholesterol varies among individuals. [35][36][37] As a group, our FH subjects (Table 2) responded to the NCEP-I diet with 15% and 17% reductions in total cholesterol and LDL-C, respectively, in agreement with what has been previously reported. 26 ApoA-I, apoB, and apoE are among the genetic loci that have been implicated in the variable lipidic response to dietary changes.…”
Section: Discussionsupporting
confidence: 90%
“…[23][24][25] The range of the response to changes in the amount or type of dietary fat and cholesterol varies among individuals. [35][36][37] As a group, our FH subjects (Table 2) responded to the NCEP-I diet with 15% and 17% reductions in total cholesterol and LDL-C, respectively, in agreement with what has been previously reported. 26 ApoA-I, apoB, and apoE are among the genetic loci that have been implicated in the variable lipidic response to dietary changes.…”
Section: Discussionsupporting
confidence: 90%
“…Diet studies have demonstrated that some individuals are consistent hypo-and hyperresponders to dietary cholesterol [37], although these different responses cannot be predicted. To date, only two dietary studies have been carried out to determine the association between apo A-1 promoter genotype and plasma lipid responses to dietary change [15,23].…”
Section: Discussionmentioning
confidence: 99%
“…However, when we repeated this trial 6 years later in the same volunteers with the same challenge and design [18], the correlation between an individual's response in the first and in the second study was only r = 0.32: many of the putative hyperresponders had become hyporesponders, and vice versa. The same was true for other cohorts of volunteers whom we tested repeatedly over the years [19][20][21][22]. Keys and coworkers [23], who studied one group of men on a variety of diets, also concluded that true non-responsiveness is rare if it exists at all, even though one subject may react aberrantly in one particular trial.…”
Section: Individual Responsiveness Is Partly a Statistical Artifactmentioning
confidence: 62%